(3ejKGb hdi GdReGfs ((3GdCejQ YjSi GdJfhNi s)
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce GdCMO GdaQ GdUeO , GdefRg Yf GdCRhGL hGdYOO EbQGQkG ChLHg Ydi faSg hGTgO Hg Ydi QhMg s
(3BNQgG (B:s
(3cGf ef GdehMOjf GdaGFRjf hcJH ai TgQ cPG hcPG ef SfI cPG hcPG HSja ehdGfG Ld PcQg hTO SdWGfg hMOg Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds